POSTOPERATIVE COMPLICATIONS ASSOCIATED WITH PELVIC EXENTERATION IN WOMEN WITH GYNECOLOGICAL CANCER: AN INTEGRATIVE REVIEW - Silva, Isis Ataide da; Carneiro, Irna Carla do Rosario Souza; Santana, Mary Elizabeth de; Ferreira, Ilma Pastana (Cogitare Enfermagem, 2023)
Objective: to identify the main complications arising from the pelvic exenteration surgery in gynecological cancer and the in-hospital death outcome after the surgical procedure. Method: an integrative literature review considering 23 articles published from 2012 to 2020 in the LILACS and IBECS databases. The descriptors used were the following: genital cancer, gynecological cancer, pelvic exenteration, exenteration, postoperative complications, surgical complications and death, combined by means of the AND or OR Boolean connectors. Results: surgical applicability was verified for cervical, uterine, ovarian, vaginal and vulvar cancer; age was associated with comorbidities (diabetes and hypertension); total pelvic exenteration was predominant; and there were high mean surgical and hospitalization times due to infections. Contributions to the area: this research enables improvements in the health care provided in the PE pre-, peri- and post-operative periods, as it elucidates the main problems resulting from this surgery, their stratifications and management options.